2021
DOI: 10.1021/acs.energyfuels.1c02561
|View full text |Cite
|
Sign up to set email alerts
|

Huff-n-Puff Technology for Enhanced Oil Recovery in Shale/Tight Oil Reservoirs: Progress, Gaps, and Perspectives

Abstract: In recent times, particularly in the 21st century, there has been an alarming increase in the demand for global energy, along with continuous depletion in conventional oil reservoirs. This necessity has incentivized interested scholars and operators worldwide to seek alternative oil resources. To secure such accelerating energy demand, considerable effort has been directed toward the development of previously unconventional oil formations that, in past decades, had remained sidelined. Although shale oil reserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 304 publications
1
37
0
Order By: Relevance
“…Unconventional resources, like shale reservoirs, are widely recognized for their extremely low permeability and porosity . Despite the fact that multistage hydraulic fracturing and horizontal well drilling techniques are used to extract the remaining oil from such reservoirs, only 4–6% of the trapped oil can be extracted, and the oil production drops after a few months, attributing to the ultralow permeability. Water injection is also one of the suitable strategies for increasing oil recovery from conventional reservoirs; nevertheless, due to weak injectivity, insufficient sweep potency, and clay swelling concerns, this approach is not the ideal solution for tight reservoirs. , Cyclic gas injection outperforms gas flooding methods in terms of enhancing oil recovery, mainly in ultratight reservoirs. , The total organic carbon (TOC) is the most important influencing parameter on gas injection in tight reservoirs because kerogen makes the surface of the pore oil-wet, making the oil inside challenging to extract . Due to the combination of multiphase fluids (i.e., gas, oil, condensate, and water) and scales, multiphase flow production can create a number of challenges including wax and asphaltene deposition, hydrate formation, slugging, and emulsions .…”
Section: Introductionmentioning
confidence: 99%
“…Unconventional resources, like shale reservoirs, are widely recognized for their extremely low permeability and porosity . Despite the fact that multistage hydraulic fracturing and horizontal well drilling techniques are used to extract the remaining oil from such reservoirs, only 4–6% of the trapped oil can be extracted, and the oil production drops after a few months, attributing to the ultralow permeability. Water injection is also one of the suitable strategies for increasing oil recovery from conventional reservoirs; nevertheless, due to weak injectivity, insufficient sweep potency, and clay swelling concerns, this approach is not the ideal solution for tight reservoirs. , Cyclic gas injection outperforms gas flooding methods in terms of enhancing oil recovery, mainly in ultratight reservoirs. , The total organic carbon (TOC) is the most important influencing parameter on gas injection in tight reservoirs because kerogen makes the surface of the pore oil-wet, making the oil inside challenging to extract . Due to the combination of multiphase fluids (i.e., gas, oil, condensate, and water) and scales, multiphase flow production can create a number of challenges including wax and asphaltene deposition, hydrate formation, slugging, and emulsions .…”
Section: Introductionmentioning
confidence: 99%
“…Although less common than CO 2 EOR, the injection of other gases such as CH 4 and nitrogen (N 2 ) is practiced in the industry, too. Compared to CO 2 , CH 4 is highly compressible and often more readily available. , CH 4 huff-and-puff injection experiments in core samples confirmed that the huff-and-puff injection operation could improve condensate oil recovery by 6%. , N 2 is relatively difficult to dissolve in crude oil and has a higher MMP than CO 2 . Therefore, the effect of N 2 injection is generally not as good as CO 2 injection.…”
Section: Application Of Phase State Study In Shale Oil Explorationmentioning
confidence: 99%
“…With the continuous depletion of conventional oil and gas resources and the huge demand for oil and gas resources due to rapid economic development, the exploration and development of unconventional oil and gas resources have become more and more important. In recent years, the Tuha oilfield has conducted a lot of geological exploration and oil and gas testing in the Santanghu Basin in northeastern Xinjiang, China, and finally discovered a new type of tight oil reservoirs, called tight sedimentary tuff reservoirs (TSTRs). The formation of TSTRs is closely related to volcanic eruption and lake-basin deposition of volcanic ash. The exploration and development results show that TSTRs are significantly different from conventional tight oil reservoirs in terms of the reservoir-forming model, lithology, physical properties, and fluid properties. …”
Section: Introductionmentioning
confidence: 99%